Monitoring Total Water Storage Changes with GRACE Mission and GLDAS Model and Effect of Climatic Factors on These Changes: Case Study in Konya Basin - Emel Zeray Öztürk (Doğal Afetler ve Çevre Dergisi)
The climate changes observed in recent years require the efficient use of water resources. In this respect, policies followed for sustainable water management necessitate continuous monitoring of water mobility. In recent years, it is possible to produce maps for the monitoring of water resources, trend estimations and visualization of changes in water areas, with remote sensing technology. Especially with the integration of satellite gravimetry and global hydrological models, these studies can be carried out relatively quickly and at low cost. In this study, water storage changes (TWSA: Total Water Storage Anomaly) in the region of Konya basin were evaluated using the GRACE (Gravity Recovery and Climate Experiment) satellite mission and GLDAS (Global Land Data Assimilation System) data. In addition, the short and long term effects of climate changes on the results have been investigated. The results show that between 2002 and 2020, groundwater and, accordingly, the total water storage changes have a negative trend in the long term, in the study area. Additionally, it can be deduced that TWSA and climatological variables including precipitation and temperature have a high correlation at 2- and 3-month lags.